The Influence of Financial Literacy and Digital Literacy on Mobile Banking Adoption - Sabila, Varania Pambagyo; Hasnawati, Hasnawati (Syntax Literate, 2024)
This research examines the influence of Financial Literacy and Digital Literacy on Mobile Banking Adoption in Jabodetabek. This research data was obtained using a questionnaire in the form of a Google form and distributed via the WhatsApp friendship network and other social media such as TikTok and Instagram. The respondent criteria for this research are bank customers who are over 20 years old, have a mobile banking application, and actively use the mobile banking application for daily transactions. A total of 210 answers have been filled in and all answers have met the requirements for processing. This research observes that there is a significant influence of Financial Literacy and Digital Literacy on Mobile Banking Adoption. The dependent variables, namely Perceived Ease of Use, Perceived Usefulness, and Relative Advantage, have high explanatory power of the model. The independent variables Financial Literacy and Digital Literacy have a strong influence on the three dependent variables of this research, showing that Financial Literacy and Digital Literacy have a direct or positive influence on the use of Mobile Banking.